2006
DOI: 10.1128/mcb.00043-06
|View full text |Cite
|
Sign up to set email alerts
|

Mouse emi1Has an Essential Function in Mitotic Progression during Early Embryogenesis

Abstract: For successful mitotic entry and spindle assembly, mitosis-promoting factors are activated at the G 2 /M transition stage, followed by stimulation of the anaphase-promoting complex (APC), an E3 ubiquitin ligase, to direct the ordered destruction of several critical mitotic regulators. Given that inhibition of APC activity is important for preventing premature or improper ubiquitination and destruction of substrates, several modulators and their regulation mechanisms have been studied. Emi1, an early mitotic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 39 publications
3
29
1
Order By: Relevance
“…Moreover, we found no obvious phenotype in salivary gland cells mutant for rca1. The result that Rca1 activity is required in mitotic but not in endoreplicating cells is consistent with the phenotype of Emi1-deficient mice, in which the mitotic cells of the inner cell mass cells die, whereas the endoreplicating trophoblast giant cells appear normal (Lee et al 2006). Therefore, CycE-Cdk2 is the only known APC/C-Fzr inhibitor in larval salivary glands.…”
Section: Cyce-cdk2 Regulates Apc/c-fzr Activity In Salivary Glandssupporting
confidence: 80%
“…Moreover, we found no obvious phenotype in salivary gland cells mutant for rca1. The result that Rca1 activity is required in mitotic but not in endoreplicating cells is consistent with the phenotype of Emi1-deficient mice, in which the mitotic cells of the inner cell mass cells die, whereas the endoreplicating trophoblast giant cells appear normal (Lee et al 2006). Therefore, CycE-Cdk2 is the only known APC/C-Fzr inhibitor in larval salivary glands.…”
Section: Cyce-cdk2 Regulates Apc/c-fzr Activity In Salivary Glandssupporting
confidence: 80%
“…EMI1 depletion in human cells and zebrafish leads to increased cell size, while FACS analysis of human cell lines, as well as zebrafish cells, in the present study indicated that this factor is essential for inhibiting rereplication (6,21,39,42). It is likely that our observation of rereplicated and unsegregated chromosomes or polyploid karyotypes has not been reported before because knockdown of EMI1 in human cell lines induces senescence and the murine Emi1 knockout has a very early lethal phenotype (17,39). Nonetheless, we have shown that emi1 depletion is a mechanism for the genesis of near-tetraploid cells, suggesting that emi1 m/m zebrafish may be a useful model for examining the molecular mechanism regulating this process and the ensuing cellular consequences, such as the derivation of aneuploid cells, as well as identifying additional mechanisms through which emi1 may contribute to leukemogenesis.…”
Section: Discussionmentioning
confidence: 41%
“…Knockout of murine Emi1 results in an embryonic-lethal phenotype prior to implantation, while a deficiency of Emi1 in cultured pronuclear zygotes leads to multipolar and tangled spindle structures, orphan chromosomes, large nuclei, and apoptosis by the 16-cell stage (17). Otherwise, the dynamic influence of EMI1 on early vertebrate development remains undefined.…”
mentioning
confidence: 99%
“…In addition, early embryogenesis was examined using mice deficient in Emi1, which is known to be an APC/C inhibitor (Reimann et al, 2001). Although Emi1 −/− embryos form polyploid TGCs, the inner cell mass does not develop properly, presumably because of the high degree of polyploidy and the abnormal cell-cycle progression (Lee et al, 2006). By contrast, Skp2 appears to be less crucial than Cdh1.…”
Section: Cdh1mentioning
confidence: 99%